(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2025)
The Venezuelan economy has experienced profound transformations and significant challenges in the period between November 2019 and October 2024. Various economic theories offer explanations for the factors that influence inflation, including the quantity theory of money, the theory of demand and aggregate supply, the theory of rational expectations, the theory of demand inflation and the theory of cost inflation. Financial security is a fundamental pillar to achieve general well-being. The research focuses on analyzing the relationship between inflation and other key macroeconomic variables, such as the exchange rate, international reserves, interest rates and the investment index in the context of the Venezuelan economic environment. A quantitative approach is used using the Excel data analysis tool to perform multiple linear regression and scatter plots, in order to identify the relationships between the variables and quantify the impact of the variables on the INPC. The results obtained show a strong positive correlation between the INPC and key variables. The study highlights the complexity of the Venezuelan hyperinflationary crisis, showing the need for comprehensive economic policies that address not only the symptoms, but also the underlying structural causes.